Aggression and aspects of impulsivity in wild‐type rats. Issue 4 (24th January 2014) - Coppens, Caroline M.; de Boer, Sietse F.; Buwalda, Bauke; Koolhaas, Jaap M.
<x xml:space="preserve">Abstract</x> Aggression is closely related to impulsive behavior both in humans and in animals. To avoid potential negative consequences, aggressive behavior is kept in control by strong inhibitory mechanisms. Failure of these inhibitory mechanisms results in violent behavior. In the present experiments, we investigated whether aggressive behavior is related to impulsive behavior. Furthermore, we investigated if violent behavior can be distinguished from "normal" aggressive behavior in terms of impulsivity levels. We used rats of the wild‐type Groningen strain, rats of this strain differ widely in their level of offensive aggression expressed toward an unfamiliar intruder male, ranging from no aggression at all to very high levels of intense and sometimes violent behavior. Violent behavior was displayed by some of the animals that were given repeated winning experience. We used behavioral performance in an unpredictable operant conditioning paradigm for food reinforcement (variable interval 15) and performance in a differential‐reinforcement of low rate (DRL‐60s) responding as determinants for impulsivity. We predicted that offensive aggression is correlated with behavioral flexibility measured by the VI‐15 procedure and that aggressive behavior is characterized by low behavioral inhibition on the DRL task. In addition we expected that violent animals would be characterized by extremely low levels of behavioral inhibition on the DRL task. We showed that the level of offensive aggression indeed positively correlated with VI‐15 performance. In addition, we showed that behavioral performance on the DRL procedure is similar in low and high aggressive rats. However, violent animals can be dissociated by a lower efficiency of lever pressing on a DRL‐60s schedule of reinforcement. Aggr. Behav. 40:300–308, 2014. © 2014 Wiley Periodicals, Inc.